(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the frequency of people using iodized salt and to assess the awareness of people about its harmful effects. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Community Medicine, Jinnah Postgraduate Medical Centre, Karachi from February to May 2018. Materials and Methods: A study was conducted on a sample of 384 individuals. The sample was taken through Non-Probability Purposive Sampling from all the districts of Karachi. An informed verbal consent was taken from the people. A self-administered structured questionnaire was developed for the interview, Pilot study was conducted to assess the authenticity of the questionnaire. The questionnaire was then distributed, got filled, data was entered and analyzed using SPSS version 20, with 95% confidence interval and 0.05 p-value was taken as statistically significant. Results: A total of 384 adults were interviewed. Out of them 21.6% were males and 78.4% were females. Only 36.5% people were using the iodized salt while the majority i.e. 63.5% were using the salt devoid of iodine. 42.7% of the individuals knew that not using iodized salt can cause diseases, on the contrary, a significant amount i.e. 57.3% of the persons were unaware that iodine deficiency can lead to pathological issues as well. Only 47.4% people knew that iodized salt is beneficial for pregnant ladies, while just 37.5% of the respondents were aware that goiter is caused by iodine deficiency. 57.6% of the public knew that surgery is suggested by the doctor for goiter. On the other hand, only 32.0 % individuals were aware that iodine deficiency can cause stunted growth. And just 18.2% people believed that iodine deficiency can cause delayed puberty. Conclusion: The study concluded that majority of population had meager knowledge of the benefits of iodized salt and are not well aware of the outcomes of its deficiency. The main factor responsible for iodine deficiency is a low dietary supply of iodine.